(untitled) - Kawahara, Toshiaki (Tokyo,New York, 1990)
An easily read biography of the long-reigning Japanese emperor. An awkward, uncoordinated boy, Hirohito was given an imperial education. The limits placed on his power and the political machinations of his prime minister and other advisors before their declaration of war on the U. S. are clearly shown. Hirohito's own views are not available since many official records are incomplete. A listing of prime ministers and cabinets from 1913-1989 is available. Pair this book with Karen Severns' Hirohito (Chelsea House, 1988), which contains photos and an index, for good sources for reports. --Dorothy Addison, Woodlawn School, Fairfax County, VA.
Keywords: Emperors; Biography; Japan